Characterization of Chemical Quality of Tuna Fish Skin Oil (Thunnus Sp.) - Saleh, Rahmawati; Rosmaladewi, Rosmaladewi; Fattah, Nurlaeli; Laylah, Nur (Journal of Agriculture, 2024)
The chemical physical properties of tuna fish oil include 25% saturated fat, 75% unsaturated fat, density 967.96 kg/m3, iodine number 170, saponification number 188, refractive index 25 oC 1.4785, unsaponifiable number 0.1% and types of fatty acids contained in tuna fish oil, namely palmitic, stearic, oleic and linoleic acids. Tuna fish waste, which includes heads, bones and skin, if not handled, will quickly deteriorate and become rotten, so further processing is needed to be utilized as well as possible into products such as oil from tuna fish processing waste. At present, oil from tuna fish waste, which is a derivative product of tuna fish with selling value, has not been widely developed and commercialized. Therefore, a more in-depth study of the processing of tuna fish waste is needed, including to determine the physico-chemical properties contained in oil from tuna fish waste. This study aims to analyze how the value of refractive index, peroxide number, free fatty acids and iodine number in tuna fish skin oil. The results showed that the chemical quality characterization of tuna fish skin oil obtained a refractive index value of 1.638, free fatty acids (FFA) 0.03%, peroxide number 0.2 meq / kg material and Iod number 44.74 g I2 / 100 g material.